STUDI POLITIK HUKUM TERKAIT PASAL 79 UNDANG-UNDANG NOMOR 11 TAHUN 2020 TENTANG CIPTA KERJA KLASTER PERBANKAN SYARIAH - Sulaiman Kurdi; Abdul Ghofur; Ichwan Ahnaz Alamudi (Universitas Islam Negeri Mataram, 2023)
This research was motivated by the birth of the job creation law in 2020 which regulates many things including Islamic banking in Article 79. This article adds to the long list of laws and regulations on Islamic banks that have existed since almost 30 years ago (1992). Researchers want to know whether there are significant changes contained by this article and whether the legal politics of Islamic banking has changed with the birth of this job creation law. This research is a type of literature study or in the legal world is called juridical-normative legal research. This study shows that Article 79 of the job creation Law No. 11 of 2020 has a combination of properties between responsive and elitist legal products, built on the desire to develop the Islamic economy as part of National Economic Development. This article contains changes to the maximum ownership of Islamic commercial banks by foreign parties, which was originally in law No. 21 of 2008 regulated by Bank Indonesia regulations, now following the laws and regulations in the field of investment. The legal politics behind the job creation law on aspects of Islamic banking is the same as other aspects, namely inviting investors not only from within but also from abroad to invest in Indonesia. This means that the government wants to open up investment space in the Islamic banking sector wider than ever.